1998
DOI: 10.1177/104063879801000303
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Ki-67 and PCNA in Canine Mammary Tumors: Relationship to Clinical and Pathologic Variables

Abstract: The objectives of this study were to measure the proliferation indices in canine mammary tumors using immunohistochemical detection of Ki-67 and proliferating cell nuclear antigen (PCNA), to determine the relationship of these antigens to clinical and pathologic variables, and to investigate the usefulness of these antigens as prognostic indicators. Ninety-six female dogs with 115 primary nonmetastasized spontaneous mammary tumors and dysplasias were included in the study. Immunostaining was performed using MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
138
1
26

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(193 citation statements)
references
References 33 publications
28
138
1
26
Order By: Relevance
“…More recently, other authors have tried to relate cell proliferation markers with the diagnosis, prognosis and outcome of breast neoplasms (Pena et al 1998, Zacchetti et al 2003, Kushlinskii et al 2004, Zuccari et al 2004, Nowak et al 2006. Nowak et al (2006) confirmed the relationship between Ki-67 and PCNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, other authors have tried to relate cell proliferation markers with the diagnosis, prognosis and outcome of breast neoplasms (Pena et al 1998, Zacchetti et al 2003, Kushlinskii et al 2004, Zuccari et al 2004, Nowak et al 2006. Nowak et al (2006) confirmed the relationship between Ki-67 and PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported the value of these nuclear antigens in the prediction of disease-free interval and overall survival as independent prognostic factors in multivariate analyses (Takeishi 1991, Wintzer et al 1991, Veronese et al 1993, Rabenhorst et al 1994, Delahunt et al 1995, Pena et al 1998, Fitzgibbons et al 2000. Other authors have reported inconsistent results (Thomas et al 1993, Gasparini et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that infiltrative growth, vascular/lymphatic invasion, and lymph node metastasis are good criteria for indicating malignant behavior in canine mammary carcinomas. 6,8 The Ki-67 labeling index, known as an independent and objective prognostic factor in disease-free and overall survival, 8 was also higher in true SSC (mean rate: 31%; Fig. 10) compared with MM and BC (25% and 21%, respectively; SSC vs BC, P < .01).…”
mentioning
confidence: 99%
“…The mortality rate of grade III tumours was also 7 times higher than that of grade II tumours. In another study, Pena et al (18) reported that increased Ki-67 expression was an objective prognostic parameter in predicting the postsurgical behaviour of canine mammary carcinomas, but it was not objective prognostic parameter for predicting metastases, disease free survival, and overall survival. Graham and Myers (10) stated that IMD was higher in metastatic tumours than benign tumours, but there was no significant difference between malignant tumours with and without metastases.…”
Section: Discussionmentioning
confidence: 99%